New Locality of the endangered Sierra Madre Sparrow (Xenospiza Baileyi) from the State of Durango, Mexico, and recommendations for its conservation - Martínez-Guerrero, José Hugo; Nocedal, Jorge; Sierra-Franco, Daniel; Arroyo-Arroyo, Samuel Ignacio; Pereda-Solís, Martín Emilio (Instituto de Ecología, A.C., 2018)
The Sierra Madre Sparrow (Xenospiza baileyi) is an endemic species of Mexico that is threatened with extinction. Its distribution is reported in two areas: One in the Transvolcanic Belt of central Mexico (La Cima) near Mexico City and the other in the Sierra Madre Occidental in northwestern Mexico (Ejido Ojo de Agua El Cazador) near the city of Durango, in the state of Durango. The habitat is the same in these two areas, and consists of sub-alpine grassland that is located in shallow valleys or shallows. In our case, "El Bajío la Cantera" of approximately 55 hectares, is mostly used in rainfed agriculture, protected from livestock grazing with wire fences, which in turn represents protection for remnants of grassland where they are the birds. “El Bajío la Cantera" belongs to Ejido 12 de Mayo, Municipality of San Dimas, Durango, where 28 males were detected singing along a 500 meter transect. This finding represents the population of the healthiest Sierra Madre Sparrow currently known, so it would be necessary to document their population trend over time. This information can help to evaluate and propose the creation of a special protection area for the species that involves joint government actions and ejidatarios tending to conserve the habitat during the reproductive season in order to increase and / or maintain the size of the population.